Active damping of rotational load oscillations at container cranes by individual rope length actuation. Issue 1 (December 2013) - Kreuzer, Edwin; Radisch, Christian
Abstract A particular challenge in the field of container crane control are rotations of the load about its vertical axis when neither special rotational actuators nor variable configurations of the rope directions are available. It is possible to enhance damping of rotational load oscillations by changing the rope lengths individually. Under the assumption of rigid ropes, a model representing the approximate dynamical behavior of the oscillator with three degrees of freedom is developed which reflects the nonlinear coupling effects between the degrees of freedom. This model is used for a stabilizing controller design with only the position of the trolley and the rope lengths actuated. (© 2013 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)